Initial (“reduced”) forms of participation in the commission of genocide in the Criminal Code of the Republic of Kazakhstan - Amanzholov, Zh.M.; Adibayeva, A.K. (Bulletin of the Karaganda University “Law Series”, 2021)
The article examines the principal aspects of the implementation of the norms of the Convention of the United Nations on Genocide in the Criminal Code of the Republic of Kazakhstan in designations of the initial punishable forms of participation in the commission of this international crime. In this regard, the authors analyzed the ratio of articles of both the universal international agreement and the criminal law of the Republic of Kazakhstan from the point of view of conformity with each other using the decision of international ad hoc criminal tribunals for the former Yugoslavia and Rwanda. Special attention was paid to the fact that the current Criminal Code of the Republic of Kazakhstan, contempt’s integration of general provisions on criminal responsibility for their commission does not accommodate formal adaptation of the norms of the Convention on conspiracy and public and direct incitement to commit genocide, attempted genocide and complicity. It is emphasized that given sufficient availability of international case law on these truncated compositions, the Republic of Kazakhstan, as a State party of the Convention, has a need and opportunity to provide them in a special part of the Criminal Code as independent features of the objective side of the crime of genocide.